2019
DOI: 10.3390/electronics8111246
|View full text |Cite
|
Sign up to set email alerts
|

Broadband High-Gain Antenna for Millimetre-Wave 60-GHz Band

Abstract: This paper focuses on the 60 GHz band, which is known to be very attractive for enabling next-generation abundant multi-Gbps wireless connectivity in 5G communication. We propose a novel concept of a double-layer antenna, loosely inspired from standard log-periodic schemes but with an aperiodic geometry, reduced size, and a limited number of elements while achieving excellent performance over the entire 60 GHz band. To maximize the antenna's efficiency, we have developed a design that differs from those tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Since the physical dimensions of the antenna is maintained unaltered, the higher the frequency, the lower the wavelength, the higher the electrical dimensions of the antenna structure, hence the gain increases. [25], [26] The two-dimensional radiation pattern at two different frequencies 5. is linearly polarized and the axial ratio is over 3dB over the whole band. [27] Notice the a fair agreement between the measured and simulated patterns.…”
Section: A Antenna Operating In Microwave Band (55-95) Ghzmentioning
confidence: 99%
“…Since the physical dimensions of the antenna is maintained unaltered, the higher the frequency, the lower the wavelength, the higher the electrical dimensions of the antenna structure, hence the gain increases. [25], [26] The two-dimensional radiation pattern at two different frequencies 5. is linearly polarized and the axial ratio is over 3dB over the whole band. [27] Notice the a fair agreement between the measured and simulated patterns.…”
Section: A Antenna Operating In Microwave Band (55-95) Ghzmentioning
confidence: 99%
“…Recently, various studies have been reported in literature to develop an effective antenna for the V-band communication spectrum [15][16][17][18][19][20][21][22][23][24][25][26]. In [15], a compact size button antenna for wearable applications is proposed; however, the antenna performance parameters, including bandwidth and gain, are compromised to achieve an electrically small antenna.…”
Section: Introductionmentioning
confidence: 99%
“…Although the antenna offers compact size and wideband, it also exhibits several drawbacks, including negative gain and high profile. Similarly, [19] presents another wideband antenna, where researchers designed log-periodic antenna using multiple layers to enhance the bandwidth and gain of the proposed antenna, which resulted in a complex geometrical structure along with high profile. In another work [20], an Ultra-Wide Band (UWB) antenna is designed using the concept of fractal structures and this antenna structure offers 20 GHz of operational bandwidth with a peak gain of 4 dB.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is essential to reduce the sidelobe level (SLL) to improve the carrier-to-interference ratio (CIR) and hence the overall system capacity. The SLL can be reduced by several techniques and algorithms such as the tapered amplitude windows [11][12][13][14][15][16][17][18] and advanced evolutionary optimization techniques [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Tapered beamforming applies various amplitude feeding windows to any array geometry which effectively reduces the SLL (with some increase in the main lobe beamwidth).…”
Section: Introduction 1background and Motivationmentioning
confidence: 99%